THE SUGGESTION OF SOME COMPARATIVE EUROPEAN GROUP CORPORATE GOVERNANCE STANDARDS AFTER FINANCIAL CRISIS, CORPORATE SCANDALS AND MANIPULATION. Issue 1 (2016) - Huy, Dinh Tran Ngoc
No abstract available